Micro-rhizomes technology for healthy planting material of ginger and turmeric - Aravind, Sharon; E, Nisthar; Srinivasan, V; Kandiannan, K; Babu, K Nirmal (Indian Horticulture, 2023)
This article describes the methodology for disease free planting material production in ginger and turmeric. The propagation of two important medicinal plants- ginger and turmeric is through rhizomes which may harbour pests and disease-causing pathogens that affect crop establishment, growth and yield. Hence, use of good quality disease free seed rhizomes plays an important role in successful ginger and turmeric production. In vitro micro-rhizome technology can contribute substantially in increasing ginger and turmeric production in the country.